Slovakia's Foreign Policy in Stopping Military Aid Shipments to Ukraine - Oktaviani, Diva Rahma; Sudrajat, Lira Amalia Sucihati (Dinasti Research, 2024)
Foreign policy refers to a series of decisions and actions taken by a country to establish relations with other countries. The change in parliamentary positions in Slovakia influenced its foreign policy. Slovakia's internal political turmoil made Slovakia's foreign policy play a significant role in halting military aid deliveries to Ukraine, reflecting the complex geopolitical dynamics in Eastern Europe. This decision is reflected in Slovakia's foreign policy analysis, emphasizing the importance of maintaining diplomatic balance among regional powers. Involving both security and diplomatic aspects, this policy reflects Slovakia's discomfort in getting directly involved in regional conflicts, especially given the detrimental impact it could have on relations with neighboring countries. Abstaining from sending military aid to Ukraine demonstrates Slovakia's efforts to maintain neutrality and avoid confrontation amid tensions between Russia and Ukraine. Despite international pressure to participate in efforts to assist Ukraine, Slovakia'sforeign policy affirms its priority on regional stability and maintaining sustainable diplomatic relations. As such, it reflects a long-view strategy considering long-term regional stability and security implications.